PERAN KEPALA DESA DALAM MENINGKATKAN KESADARAN WAJIB PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN: DI DESA CIPUTRI KECAMATAN KADUHEJO KABUPATEN PANDEGLANG - Wulansari, Alfeni; Aulawi, Anton (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2025)
This research was conducted in Ciputri Village, Kaduhejo District, Pandeglang Regency to determine the Role of the Head of Ciputri Village in Increasing the Awareness of Rural and Urban Land and Building Taxpayers in Ciputri Village, Kaduhejo District, Pandeglang Regency, and to determine the factors that hinder Taxpayers from paying Rural and Urban Land and Building Tax in Ciputri Village, Kaduhejo District, Pandeglang Regency. The research method used is descriptive with a qualitative approach. Data collection methods used in this study are observation, interviews, and documentation. Data processing used in this study is triangulation then analyzed by data reduction, display data, and verification data. The results of this study conclude that Taxpayer Awareness in Ciputri Village has decreased because the realization of PBB-P2 revenues does not match the set target. Factors that hinder Taxpayers from paying PBB-P2 in Ciputri Village are caused by two factors, namely endogenous factors (internal factors) and exogenous factors (external factors). Endogenous factors in the form of low awareness of taxpayers paying PBB-P2 tax are caused by the lack of intention and no willingness of Taxpayers to pay PBB-P2 on time. Exogenous factors are economic factors because taxpayers in Ciputri Village are categorized as poor. The role of the Ciputri Village Head as the leader of the village-level government is as a motivator, who motivates to increase the awareness of the community or residents of Ciputri Village to want to pay PBB-P2 routinely and on time. The Village Head has carried out his role well by carrying out his duties as a motivator where the Village Head always provides encouragement, fosters, and influences villagers who are Taxpayers to pay PBB-P2 on time.